2009
DOI: 10.1037/a0017059
|View full text |Cite
|
Sign up to set email alerts
|

Testing a model of change in the experiential treatment of depression.

Abstract: In this study, we measured emotional processing and the alliance across 3 phases of therapy (beginning, working, and termination) for 74 clients who each received brief experiential psychotherapy for depression. Using path analysis, we proposed and tested a model of relationships between these 2 processes across phases of therapy and how these processes relate to predict improvement in the domains of depressive and general symptoms, self-esteem, and interpersonal problems after experiential treatment. Both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
84
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(99 citation statements)
references
References 71 publications
11
84
2
2
Order By: Relevance
“…The general idea is that more emotional processing leads to better outcomes, the opposite being true in the case of high avoidance levels (Hayes, Beevers, Feldman, Laurenceau, & Perlman, 2005;Pos, Greenberg, & Warwar, 2009). In other words, psychotherapy is more likely to be successful if clients express their feelings and are able to face their issues, which Hunt (1998) aptly summarised by saying "the only way out is through."…”
Section: Introductionmentioning
confidence: 99%
“…The general idea is that more emotional processing leads to better outcomes, the opposite being true in the case of high avoidance levels (Hayes, Beevers, Feldman, Laurenceau, & Perlman, 2005;Pos, Greenberg, & Warwar, 2009). In other words, psychotherapy is more likely to be successful if clients express their feelings and are able to face their issues, which Hunt (1998) aptly summarised by saying "the only way out is through."…”
Section: Introductionmentioning
confidence: 99%
“…The Experiencing Scale is an ordinal measurement system that evaluates the degree to which clients are actively engaged in productive experiential meaning-making during therapy sessions. Good levels of inter rater agreement for the Experiencing Scale had been established by Pos, Greenberg and Warwar (2009) who reported that higher level Experiencing scores significantly predicted positive treatment outcomes for clients undergoing EFT of depression.…”
Section: Internal and Reflexive Narrative Sequence Analyses: Investigmentioning
confidence: 99%
“…However, the expression of emotion in itself might not be sufficient. Research also emphasizes the fact that the 17 specific ways in which patients attend and symbolize emotional activation is related to the therapeutic outcome of treatment (Auszra, Greenberg, & Herrmann, 2013;Pos, Greenberg, & Warwar, 2009), suggesting that the way in which one comprehends and expresses emotions is also important.…”
Section: Emotional Processing In Psychotherapymentioning
confidence: 99%
“…It also seems that this increase in arousal is related to better outcome (Missirlian et al, 2005;Pos et al, 2017). Furthermore, it seems that too high or too low levels of arousal are less productive with regard to treatment outcome (Carryer & Greenberg, 2010); further, it seems that emotional arousal is more productive under a good working alliance (Iwakabe et al, 2000;Pos et al, 2009). …”
Section: Emotional Processing In Eftmentioning
confidence: 99%
See 1 more Smart Citation